The Comparison of Ferrous Sulphate and Ferric Polymaltose Treatment Efficacy of Iron Deficiency Anemia - Elkiran, Tamer; Celebi, Harika; Aygen, Bilge (Annals of Medical Research, 2021)
None
Keywords: Iron deficiency anemia, Ferrous sulphate, Ferric polymaltose